2014
DOI: 10.1136/thoraxjnl-2014-206284
|View full text |Cite
|
Sign up to set email alerts
|

Improving care for patients with idiopathic pulmonary fibrosis (IPF) in the UK: a round table discussion

Abstract: This article is the result of a round table discussion held at BMA House. Its purpose is to outline the challenges facing both patients and doctors in managing idiopathic pulmonary fibrosis. A number of recommendations for service development and research have been identified. TABLE DISCUSSION BACKGROUND TO THE ROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…As discussed in the introductory section, it has not been demonstrated that this approach results in improved survival or QoL for IPF patients; nevertheless, experts recommend this approach for IPF patients in tertiary reference centres for ILDs, mainly based on the experience derived from cancer and other progressive diseases [19]. A very important task for the multidisciplinary/interdisciplinary teams will be to show how this approach is beneficial for IPF patients and eventually to explore the possibility of delegating some of its components to healthcare players in the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As discussed in the introductory section, it has not been demonstrated that this approach results in improved survival or QoL for IPF patients; nevertheless, experts recommend this approach for IPF patients in tertiary reference centres for ILDs, mainly based on the experience derived from cancer and other progressive diseases [19]. A very important task for the multidisciplinary/interdisciplinary teams will be to show how this approach is beneficial for IPF patients and eventually to explore the possibility of delegating some of its components to healthcare players in the field.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three radiologists, one pathologist and one physiologist work closely with the team, taking regular part in monthly multidisciplinary conferences. The costs of this approach are high, and policies and guidelines recommend it only in tertiary, specialised reference centres [19], where patients with relatively rare diseases should be referred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, we have been asked on several occasions whether this phenomenon can perhaps also explain another apparent anomaly between these two trials, and a challenge in interpretation, namely the "mixed results in terms of … exacerbations" [3]. Indeed, the effects of treatment on investigator-reported acute exacerbations between the INPULSIS-1 and INPULSIS-2 trials were also heterogeneous [1].…”
mentioning
confidence: 99%